Role and Significance of Info graphics in Handbook Manuals for Performance Accountability in Planning Departments - Jagtap, Rutuja Deshmukh; Singh, Devendra Pratap (The journal of contemporary issues in business and government, 2021)
Handbooks and manuals are noteworthy tools for the guidance of the functioning of any product or process. Human beings to function optimally have varied needs. The physiological needs which are required to be fulfilled are hunger, thirst and sleep while the psychological needs are autonomy, competence and relatedness. The paper puts forth that the important prerequisite of the content of any handbook manual is to satisfy the psychological necessities. The paper attempts to review different formats of operational manuals to study and understand their effectiveness. The paper concludes that graphics contribute strongly and are appropriate apparatuses to convey information.